Liturgy and secularism: beyond the divide - Geldhof, Joris (Liturgical Press Academic, 2018)
Positioning the liturgy in the world -- Liturgy, modernity, and secularization -- Liturgy, ideology, and politics -- Liturgy beyond sacred and profane -- Positioning the world in the liturgy -- Liturgy, desacralization, and sanctification -- Retrieving the liturgical movement -- The liturgy's critical potential -- Concluding observations